Ali Asghar Engineer's Thoughts on Liberation Theology and Its Implications for Islamic Education - Fikri, Ziad; Qorib, Muhammad (Journal of English Language and Education, 2025)
Contemporary Islamic education in Indonesia faces a fundamental crisis characterized by three main problems: educational goals oriented to ritual obedience without critical awareness of social injustice, a curriculum dominated by normative-doctrinal approaches without integration of contemporary social reality analysis, and authoritarian learning processes that do not provide space for critical thinking. This research aims to analyze Ali Asghar Engineer's thoughts on liberation theology and its relevance to the transformation of contemporary Islamic education. The research method uses a qualitative approach with library research and philosophical analysis of Engineers' thinking through primary and secondary sources. The findings show that Engineer's liberation theology is built on three fundamental pillars: monotheism as a theological foundation that rejects servitude other than God, movement as an instrument of practical change, and social justice as the ultimate goal. Implications for Islamic education include: (1) the transformation of educational goals from ritualistic to transformative-liberative that results in a critical awareness of social injustice, (2) the reconstruction of the liberative curriculum with an Engineer hermeneutic approach that distinguishes normative (justice, equality, peace) and contextual elements in the Qur'an, (3) the implementation of liberating values (justice, equality, anti-discrimination, freedom of critical thinking) through methodology Dialogical-Democratic Learning. This research contribution provides a theoretical-practical framework for the development of Islamic education that is responsive to contemporary challenges such as radicalization, social inequality, and gender discrimination, and enriches liberation theology discourse in the Islamic tradition with a focus on educational applications that have not been explored much in previous research.